PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS AHASLIDES DI SDN 5 MOOTILANGO, GORONTALO - Ajengsari, Desti; Pomalingo, Samsi; Nurainun, Nurainun (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to develop interactive learning media based on Ahaslides at SDN 5 Mootilango, Gorontalo, using the Research and Development (R&D) methodology. The development process follows the 4-D model, which consists of four stages: define, design, develop, and disseminate. In the define stage, the researcher identifies the needs for effective learning media. During the design stage, the researcher creates 20 slides covering the general definition of norms, religious norms, politeness, indecency, and law, as well as interactive videos and quizzes. The develop stage involves creating and testing the media to ensure its functionality, while the disseminate stage focuses on distributing and utilizing the media among teachers and students. Evaluation results indicate that this interactive learning media allows teachers to monitor student participation in real-time. From the feasibility validation conducted by three expert validators in the fields of content, media, and psychology, the Ahaslides media received an average score of 95.56%, indicating that it is highly suitable for use. This research makes a significant contribution to the development of interactive and effective teaching methods, offering innovative solutions to enhance student engagement in the learning process.